The Investigation on The Effect of Vehicles Speed to The Pavement Performances of Malaysian Road - Zainal Abidin, Siti Yusrina (Universiti Teknologi PETRONAS, 2020)
This study is to investigation the impact of vehicle speed on the pavement performances in Malaysian Road. Most of the previous study to measure the performance of pavement are not considering speed parameter. Speed might give impact to the better performance of pavement due to the loading time from the vehicle to give impact to the pavement structure. To cater this design parameter, this study will focus on the speed parameters and the effect of it toward the mechanical properties of the bituminous material and the design life of the pavement structure. Mechanical Empirical Design Method are applied to get the input data and analysis where the design method used is Nottingham’s Design Method are adapted to this study to get the analysis done. Secondary data are used to input the parameter in the BISAR Software to simulate on the impact of the speed to the properties of the material and design life of the structure.